Laser diode arrays based on AlGaAs/GaAs quantum-well heterostructures with an efficiency up to 62%. (September 2017) - Ladugin, M.A.; Marmalyuk, A.A.; Padalitsa, A.A; Telegin, K.Yu.; Lobintsov, A.V.; Sapozhnikov, S.M.; Danilov, A.I.; Podkopaev, A.V.; Simakov, V.A.
Abstract: The results of development of quasi-cw laser diode arrays operating at a wavelength of 808 nm with a high efficiency are demonstrated. The laser diodes are based on semiconductor AlGaAs/GaAs quantum-well heterostructures grown by MOCVD. The measured spectral, spatial, electric and power characteristics are presented. The output optical power of the array with an emitting area of 5 × 10 mm is 2.7 kW at a pump current of 100 A, and the maximum efficiency reaches 62%.